2013
DOI: 10.1038/ng.2800
|View full text |Cite
|
Sign up to set email alerts
|

Frequent truncating mutations of STAG2 in bladder cancer

Abstract: Here we report the discovery of truncating mutations of the gene encoding the cohesin subunit STAG2, which regulates sister chromatid cohesion and segregation, in 36% of papillary noninvasive urothelial carcinomas and 16% of invasive urothelial carcinomas of the bladder. Our studies suggest that STAG2 plays a role in controlling chromosome number but not proliferation Users may view, print, copy, download and text and data-mine the content in such documents, for the purposes of academic research, subject alway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
138
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(156 citation statements)
references
References 13 publications
13
138
5
Order By: Relevance
“…Such trends will undoubtedly continue in the years to come. It will also be important to determine to what extent mutations or misregulation of cohesin and condensin subunits might contribute to human cancers (Ham et al 2007;Balbás-Martínez et al 2013;Guo et al 2013;Kon et al 2013;Solomon et al 2013). Third, and, finally, all issues described above need to be addressed, also, from an evolutionary point of view.…”
Section: Resultsmentioning
confidence: 99%
“…Such trends will undoubtedly continue in the years to come. It will also be important to determine to what extent mutations or misregulation of cohesin and condensin subunits might contribute to human cancers (Ham et al 2007;Balbás-Martínez et al 2013;Guo et al 2013;Kon et al 2013;Solomon et al 2013). Third, and, finally, all issues described above need to be addressed, also, from an evolutionary point of view.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in cohesion genes could therefore lead to CIN by different mechanisms: mis-segregation of chromosomes followed by aneuploidy due to partial or total loss of cohesion or as a consequence of impaired DNA repair as well as altered gene expression. Recently, in several studies, alterations in sister chromatid cohesion genes were identified in a variety of cancers (27,(43)(44)(45)(46). In particular, inactivating alterations in STAG2 have been frequently found.…”
Section: Discussionmentioning
confidence: 99%
“…Notably recurrent mutations have been observed in acute myeloid leukemia (AML) cases de novo AML and AML with myelodysplasia-related changes (10-20%), down syndrome-associated acute megakaryoblastic leukemia (50% DS-AMKL), myelodysplastic syndromes (5-15%), and myeloproliferative neoplasms (MPNs; up to 10%), as classified according to the 2008 WHO classification for hematopoietic and lymphoid tissue (Ding et al, 2012;Cancer Genome Atlas Research Network, 2013;Kon et al, 2013;Nikolaev et al, 2013;Yoshida et al, 2013;Thol et al, 2014;Thota et al, 2014;Lindsley et al, 2015). In addition, somatic mutations have been found in a wide range of solid cancers like bladder cancer (20%) and Ewing's sarcoma (20%; Balbás-Martínez et al, 2013;Guo et al, 2013;Solomon et al, 2013;Crompton et al, 2014;Tirode et al, 2014). Besides the aforementioned somatic mutations, germline mutations of cohesin have been described in patients with developmental syndromes, particularly Cornelia de Lange syndrome (CdLS; Mannini et al, 2013).…”
Section: Cohesin Silencing Leads To Increased Replating Capacity In Vmentioning
confidence: 99%